High-temperature graphitization characteristics of vitrinite and inertinite - Zhifei, Liu; Daiyong, Cao; Gaojian, Chen; Qingtong, Chen; Zhongwei, Bi (Frontiers in Earth Science, 2023)
In order to explore the graphitization characteristic differences between vitrinite and inertinite in coal, this study conducted high-temperature thermal simulation experiments (at five temperature points: 1800 ℃, 2100 ℃, 2400 ℃, 2700 ℃, and 3000 ℃) using inertinite-rich and vitrinite-rich samples as graphitization precursors. The quantitative comparison for the evolution characteristics of their graphite lattice was carried out using high-resolution transmission electron microscopy (HRTEM), X-ray diffractometer (XRD), and Raman spectroscopy (Raman) techniques. HRTEM revealed that an evident increase in carbon layer numbers and degree of extension was observed with increasing treatment temperature. The development of the graphite structure in the inertinite-rich samples was superior to that of the vitrinite-rich samples under the same temperature conditions, this was manifested by larger graphite layer scales and straighter carbon layer stripes. XRD results showed that throughout the entire temperature range of the experiment, the d002 spacing of inertinite was always smaller than that of vitrinite, indicating a higher degree of graphitization. However, the graphitization rate of vitrinite was faster than that of inertinite from 1800 ℃ to 2700 ℃. The d002 value of the two macerals merges at 3000 ℃. vitrinite exhibited a uniform and smooth evolution state throughout the entire heating process, while inertinite exhibited an "inert" state between 1800℃ and 2100℃ (d002 values stagnated near at 0.3440 nm). Raman data indicated that with increasing simulated temperature, the defect level (R2 and R3) of vitrinite rapidly decreased below that of inertinite. Throughout the entire temperature range, vitrinite demonstrated superior defect healing ability in terms of both rate and capability compared to inertinite. Under high-temperature thermal simulation, the three-dimensional lattice construction and defect elimination of vitrinite exhibited synchronous evolution characteristics. On the other hand, the formation of the graphite lattice in inertinite showed an evolutionary trend of "first three-dimensional lattice construction, followed by gradual defect elimination".